De ator a autor do processo educativo: uma investigação interdisciplinar - José, Mariana Aranha Moreira (2011)
The formative experience focuses on how the educator builds his authorship process. The problematic investigative aims to reflect on how the theory of interdisciplinarity allows researchers, teachers trained and in training to become authors. The setting of research methodology makes use of narrative language, which is assumed as a metaphorical figure to find the concept of the legitimacy of authorship on educational issues. The dialogue between the personal and professional experiences narrated and explained creates educational realities that give shape to the investigation. For hermeneutics interprets the observed phenomena to understand the construction of knowledge as a way of being. This thesis is organized in seven sections, starting with a narrative that reflects the stages of the authorship process by encouraging their further development and discussion. The entire narrated is built from parts chosen that, according to Bruner (2001), raises interpretations. "From actor to author of the educational process" presents the methodological approach adopted. "Being an actor" begins with an extract from the book "Reinações of Narizinho," of Lobato (1988-1989), in order to enter discussions about what it means to be an actor in education. "Being author of" notes that researchers in education can be considered authors, phenomenon observed in the interpretation of dissertations and theses in the Research Line "Interdisciplinary" between the years 2000 to 2010. "From actor to author" suggests that, besides the researcher, the teacher can also be an author. The word of the teacher gives him authority over the education. Not an imposed authority, but won by his knowledge, his speech and his attitudes. For the investigative approach in the face of reality that surrounds him, the teacher assumes characteristics of authorship. "The author Interdisciplinary" dares to consider his authorship as one of the principles inherent to the Interdisciplinary Theory proposed by Fazenda (2001). "The meaning of authorship" seeks to answer one last question: "What is the meaning of being an author in education?". Refers to the signification of the concept of meaning, based on Frankl (1989a), to verify the possibility of understanding of meaning in the realization of creative, experiential and attitudinal values. The partial considerations show clearly the possibility of researchers, trained and in training teachers to be authors in education. When narrating their stories of personal and professional life can produce on another the understanding of what is done and thought about what is made by someone in building of the educational process